Experimental Study of the Classical Music and Light Intensity Effect on the Heart Rate of the Readers (A Case Study in Industrial Engineering Library, Diponegoro University) - Prastawa, Heru; Susanto, Novie; Mahachandra, Manik (Jurnal Ilmiah Teknik Industri, 2020)
This paper aims at determining the effect of music and light intensity on heart rate and perceptions of visitors in Industrial Engineering Library, analyzing the performance of users in various treatment conditions and by doing so, providing recommendations for the right combination of treatments to increase concentration and increase the level of relaxation. It proves a better performance of the students when they work in better physical environment design, especially in the library. Based on preliminary studies, it is indicated that the Industrial Engineering Library (IEL) needs re-engineering of the light and sound condition. The library room does not inline with the Head of National Library of Indonesia's rules, number 13 of 2017, about the national standard of college libraries for lighting condition. Besides, about 90.2% of students feel the classical music increases comfort and concentration in reading activities. The research data was collected by recording 24 respondents' heart rate and processed by experimental design using SPSS software. The result provides recommendations from the human physical aspect by selecting the treatment to achieve the highest performance. An additional questionnaire with a Likert scale was disseminated to measure the respondents' perceptions. The results showed that the interaction of 200-600 lux lighting and classical music variables was the best treatment to achieve the highest performance.